Economic impact of climate change and climate change adaptation strategies for fisheries sector in Fiji. (May 2016) - Dey, Madan Mohan; Gosh, Kamal; Valmonte-Santos, Rowena; Rosegrant, Mark W.; Chen, Oai Li
Abstract: Capture fisheries and aquaculture sectors have played major roles in the national economy and food security of Fiji. But climate change may place substantial stress on these sectors within this archipelago. This paper assesses the potential economic impact of two important climate change adaptation strategies in Fiji, natural resource management (NRM) and aquaculture, using a market fish supply–demand model. The model undertakes a comparative analysis of alternative fisheries development scenarios for 2035 and 2050, while taking account of the impact of climate change on the fisheries sector. The modeling and scenario analyses show that promoting aquaculture can help raise aggregate fish production, consumption, and trade. However, the required increases in aquaculture could be massive. While aquaculture development alone is unlikely to meet the growing excess demand for fish in Fiji, it will be an important component in adapting to the negative effects of climate change on capture fisheries. Various NRM strategies, such as marine protected areas (MPAs) and locally managed marine areas (LMMAs), are projected to have positive impacts in Fiji, expanding the stock and catch of fish. But current efforts on various NRM strategies are too small to have any meaningful impact to reverse the declining trends of coastal fisheries catch. Efforts would need to be greatly scaled-up to achieve significant production gains. Highlights: Analyzed economic impacts of climate change adaptation strategies on fisheries sector in Fiji. Aquaculture can help raise aggregate fish production, consumption, and trade in Fiji. Marine protected areas and locally managed marine areas have positive impacts in Fiji. Adaptation strategies need to be greatly scaled-up to achieve meaningful positive impacts.